Effect Of Giving Ricinus Comunis Leaves (Balacay) To Decrease In Body Temperature In Hypertermid Toddlers At Matanga Health Center, Banggai Laut - Yeni; Eva Agustina; Rahmania Ambarika (Universitas STRADA Indonesia, 2021)
Antipyretic administration is the main therapy in reducing hyperthermia, but excessive use of antipyretics can cause side effects. Balacay leaves have chemical content that can lower body temperature so that it has the potential as a non-pharmacological therapy for hyperthermia. The purpose of this study was to determine the effect of administering Ricinus comunis (Balacay) leaves on reducing body temperature in hyperthermic toddlers at the Matanga Health Center, Banggai Laut Regency. The design of this study was Pre Experiment with a one-group pre-post test approach. The sample studied was 61 hyperthermic toddlers determined through accidental sampling techniques. The independent variable was the administration of balacay leaves with the dependent variable being body temperature. Data collection used questionnaires and observations, the results were analyzed using the Willcoxon test at α = 0.05. The results of the study showed that all respondents had a body temperature before being given Balacay leaves in the high category, namely 61 respo Antipyretic administration is the main therapy in reducing hyperthermia, but excessive use of antipyretics can cause side effects. Balacay leaves have chemical content that can lower body temperature so that it has the potential as a non-pharmacological therapy for hyperthermia. The purpose of this study was to determine the effect of administering Ricinus comunis (Balacay) leaves on reducing body temperature in hyperthermic toddlers at the Matanga Health Center, Banggai Laut Regency. The design of this study was Pre Experiment with a one-group pre-post test approach. The sample studied was 61 hyperthermic toddlers determined through accidental sampling techniques. The independent variable was the administration of balacay leaves with the dependent variable being body temperature. Data collection used questionnaires and observations, the results were analyzed using the Willcoxon test at α = 0.05. The results of the study showed that all respondents had a body temperature before being given Balacay leaves in the high category, namely 61 respondents (100.0%) and after being given Balacay leaves, most respondents had a normal body temperature category, namely 38 respondents (62.3%) while the remaining 23 respondents (37.7%) had a high body temperature category. The results of the analysis obtained a p-value (0.000) < (0.05) so H0 was rejected, which means that there is an effect of giving Ricinus comunis leaves (Balacay) on reducing body temperature in hyperthermic toddlers at the Matanga Health Center, Banggai Laut Regency. The content of the Quercetin compound (3,4-dihydroxyflavonol) in Ricinus comunis leaves inhibits the production and release of histamine and inflammatory mediators that can trigger fever so that body temperature can slowly decrease.ndents (100.0%) and after being given Balacay leaves, most respondents had a normal body temperature category, namely 38 respondents (62.3%) while the remaining 23 respondents (37.7%) had a high body temperature category. The results of the analysis obtained a p-value (0.000) < (0.05) so H0 was rejected, which means that there is an effect of giving Ricinus comunis leaves (Balacay) on reducing body temperature in hyperthermic toddlers at the Matanga Health Center, Banggai Laut Regency. The content of the Quercetin compound (3,4-dihydroxyflavonol) in Ricinus comunis leaves inhibits the production and release of histamine and inflammatory mediators that can trigger fever so that body temperature can slowly decrease.